Facile Synthesis of Hierarchically Structured Magnetic MnO2/ZnFe2O4 Hybrid Materials and Their Performance in Heterogeneous Activation of Peroxymonosulfate - Wang, Yuxian; Sun, Hongqi; Ang, H.M.; Tade, Moses; Wang, Shaobin (American Chemical Society, 2014)
In heterogeneous catalysis for water treatment, feasible recovery of nanocatalysts is crucial to make the process cost-effective and environmentally benign. In this study, we applied two strategies, for example, magnetic separation and hierarchical structure of solid catalysts, to ensure manganese catalysts are readily separable, meanwhile their catalytic performance was retained by the nanosized structure of MnO2 nanosheets or nanorods. ZnFe2O4 was used as the magnetic core and MnO2 corolla-like sphere consisting of nanosheets, and sea-urchin shaped structure made of nanorods, were fabricated by a hydrothermal method at 100 and 140 °C, respectively. Crystalline structure, morphology and textural property of the materials were investigated. The prepared catalysts were able to effectively activate peroxymonosulfate (PMS) to generate sulfate radicals for catalytic oxidation of a typical organic pollutant of phenol. After the heterogeneous catalysis, the catalysts were easily recovered by applying an external magnetic field. The effects of temperature and repeated use on the degradation efficiencies were evaluated. The generation and evolution of sulfate radicals and phenol oxidation were studied using both competitive radical tests and electron paramagnetic resonance (EPR).